REVITALIZATION OF MANGROVE ECOTOURISM DESTINATION IN WONOREJO VILLAGE, RUNGKUT DISTRICT, SURABAYA CITY - Suyanto, Mohammad; Iswanti, Iswanti (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Tourism development has significant value for the progress of other sectors. To minimize the risks or negative impacts of the development of the tourism industry, tourism development needs to be developed according to the uniqueness and conditions of the existing region. For this reason, the concept of tourism was developed by implementing ecotourism development or sustainable tourism development, namely in the form of ecotourism. One of the manifestations of Ecotourism in Surabaya is the Wonorejo Mangrove Ecotourism The number of Wonorejo Mangrove Ecotourism tourists in 2018 was 32,015 tourists and in 2019 increased to 40,535 tourists but in 2020 decreased by 31.78%, namely as many as 12,883 tourists because in March 2020 it was closed due to the COVID-19 pandemic. In 2021 it will open and close for tourists since March 20, 2021 The research method used is a qualitative descriptive method and analytical techniques make direct observations on the condition of the object of research. By comparing the conditions before covid 19 and the conditions during the study. The results of the study during the closure of Mangrove Ecotourism that many tourist attraction facilities were damaged, especially tourist stalls, the bamboo bridge which became one of the icons in mangrove ecotourism and several jogging track locations experienced fragility. For this reason, improvements are needed in the near future to increase tourist attraction again.